CONSTITUTIONAL RESISTANCE TO EU LAW: THE COURTS AND TEST OF CONSTITUTIONAL IDENTITY CONFLICTS - Galimberti, Marco; Ninatti, Stefania (Pravni zapisi, 2020)
This essay aims to analyze how national constitutional/supreme Courts address the evolution of the European integration process when this latter touches upon fundamental constitutional elements of the EU Member States. More specifically, the paper explores the recent case law concerning the issue of constitutional identity conflicts, in order to show the common arguments underpinning different European constitutional/supreme Courts’ jurisprudence. From a comparative point of view, the analysis highlights the emergence of a growing front of constitutional resistance whose meaning for the future of European constitutionalism is still unclear. At the same time, the study seeks to examine the patterns of constitutional resistance within the European integration process in the perspective of a mutual interaction between Courts.